Abscisic acid and other plant hormones: Methods to visualize distribution and signaling. (December 2015) - Waadt, Rainer; Hsu, Po‐Kai; Schroeder, Julian I.
Abstract : The exploration of plant behavior on a cellular scale in a minimal invasive manner is key to understanding plant adaptations to their environment. Plant hormones regulate multiple aspects of growth and development and mediate environmental responses to ensure a successful life cycle. To monitor the dynamics of plant hormone actions in intact tissue, we need qualitative and quantitative tools with high temporal and spatial resolution. Here, we describe a set of biological instruments (reporters) for the analysis of the distribution and signaling of various plant hormones. Furthermore, we provide examples of their utility for gaining novel insights into plant hormone action with a deeper focus on the drought hormone abscisic acid. Abstract : Plants utilize hormones as key regulators of growth, development, and environmental adaptations. Knowledge about their cellular distribution and efficiency (signaling strength) is essential for understanding hormone‐mediated processes. Here, we discuss recent advances for the in vivo visualization of plant hormones, with deeper insights into genetically encoded reporters for abscisic acid.